2012
DOI: 10.1016/j.jbusres.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership influence on organizational performance through organizational learning and innovation

Abstract: This study analyzes the influences of transformational leadership on organizational performance through the dynamic capabilities of organizational learning and innovation. Although these indirect interrelations are very important for improving organizational performance, previous research has not usually explored them. The study confirms these influences empirically, basing the analysis on a sample of 168 Spanish firms. The results reveal that (1) transformational leadership influences organizational performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
550
3
38

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 730 publications
(625 citation statements)
references
References 107 publications
34
550
3
38
Order By: Relevance
“…Based on the views of respondents in the survey, transformational leadership explains 67.1 percent of the variance and appears as the strongest set of qualities that play a vital role for innovation. Although transformational leadership is accepted widely in the literature as a leadership style in facilitating employee creativity and organisational innovation (García-Morales et al, 2012;Shin & Zhou, 2003), consideration leadership is recognised to a lesser extent. In contrast, this study has identified consideration leadership, which explains proportions of the variance 10.5 percent, as being a complement to transformational leadership in supporting employee creativity and innovation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the views of respondents in the survey, transformational leadership explains 67.1 percent of the variance and appears as the strongest set of qualities that play a vital role for innovation. Although transformational leadership is accepted widely in the literature as a leadership style in facilitating employee creativity and organisational innovation (García-Morales et al, 2012;Shin & Zhou, 2003), consideration leadership is recognised to a lesser extent. In contrast, this study has identified consideration leadership, which explains proportions of the variance 10.5 percent, as being a complement to transformational leadership in supporting employee creativity and innovation.…”
Section: Discussionmentioning
confidence: 99%
“…Transformational leadership has generally been considered more effective than other leadership styles in facilitating employee creativity and organisational innovation (García-Morales et al, 2012;Shin & Zhou, 2003). Transformational leaders are those who inspire subordinates to perform and recognise organisational objectives and goals and have the capability to motivate followers beyond expected levels of work standards.…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Organizational learning is a well-documented determinant of desirable organizational outcomes such as financial performance, innovation capacity, and customer value (Yukl, 2009, Davis and Daley, 2008, Ellinger et al, 2002, Ellinger et al, 2003, García-Morales et al, 2012, Jiménez-Jiménez and Sanz-Valle, 2011, Baker and Sinkula, 2002, Valencia et al, 2010, Santos-Vijande et al, 2012. The rationale for attempting to improve these outcomes via improving organizational learning is that the subsequent development of new knowledge can reduce the likelihood that a company's human capital will become outdated, thus enabling the skills and knowledge to remain dynamic, and improving organizational performance (García-Morales et al, 2012).…”
Section: Improving Organizational Learning Through Leadership Trainingmentioning
confidence: 99%
“…The rationale for attempting to improve these outcomes via improving organizational learning is that the subsequent development of new knowledge can reduce the likelihood that a company's human capital will become outdated, thus enabling the skills and knowledge to remain dynamic, and improving organizational performance (García-Morales et al, 2012).…”
Section: Improving Organizational Learning Through Leadership Trainingmentioning
confidence: 99%
See 1 more Smart Citation